Type II hot corrosion screening tests of a Cr2AlC MAX phase compound - Smialek, James L.; Gray, Simon (Springer, 2018)
Low-temperature hot corrosion tests were performed on bulk Cr2AlC MAX phase compounds for the first time. This material is a known alumina-former with good oxidation and Type I high-temperature hot corrosion resistance. Unlike traditional (Ni,Co)CrAl alumina formers, it contains no Ni or Co that may react with Na2SO4 salt deposits needed to form corrosive mixed (Ni,Co)SO4–Na2SO4 eutectic salts active in Type II hot corrosion. Cr2AlC samples coated with 20K2SO4–80Na2SO4 salt were exposed to 300 ppm SO2 at 700 °C for times up to 500 h. Weight change, recession, and cross-sectional microstructures identified some reactivity, but much reduced (< 1/10) compared to a Ni(Co) superalloy baseline material. Layered Al2O3/Cr2O3 scales were indicated, either separated by or intermixed with some retained salt. However, there was no conclusive indication of salt melting. Accelerated oxidation was proposed to explain the results, and coarse Cr7C3 impurities appeared to play a negative role. In contrast, the superalloy exhibited outer Ni(Co) oxide and inner Cr2O3 scales, with Cr–S layers at the interfaces. Massive spallation of the corrosion layers occurred repeatedly for the superalloy, but not at all for Cr2AlC. This indicates some potential for Cr2AlC as LTHC-resistant coatings for superalloys.
Keywords: Cr2AlC MAX phase; Hot corrosion; Superalloys